Nature versus nurture: Have performance gaps between men and women reached an asymptote? - Millard-Stafford, M.; Swanson, A. E.; Wittbrodt, M. T. (International Journal of Sports Physiology and Performance, 2018)
Men outperform women in sports requiring muscular strength and/or endurance, but the relative influence of "nurture" versus "nature" remains difficult to quantify. Performance gaps between elite men and women are well documented using world records in second, centimeter, or kilogram sports. However, this approach is biased by global disparity in reward structures and opportunities for women. Despite policies enhancing female participation (Title IX legislation), US women only closed performance gaps by 2% and 5% in Olympic Trial swimming and running, respectively, from 1972 to 1980 (with no change thereafter through 2016). Performance gaps of 13% in elite middistance running and 8% in swimming (~4-min duration) remain, the 5% differential between sports indicative of load carriage disadvantages of higher female body fatness in running. Conversely, sprint swimming exhibits a greater sex difference than sprint running, suggesting anthropometric/power advantages unique to swim-block starts. The ~40-y plateau in the performance gap suggests a persistent dominance of biological influences (eg, longer limb levers, greater muscle mass, greater aerobic capacity, and lower fat mass) on performance. Current evidence suggests that women will not swim or run as fast as men in Olympic events, which speaks against eliminating sex segregation in these individual sports. Whether hormone reassignment sufficiently levels the playing field in Olympic sports for transgender females (born and socialized male) remains an issue to be tackled by sport-governing bodies.